Agriculture and Artificial Intelligence - Navneet Kumar, Harleen Kaur, Mansirat Kaur (International Journal of Advanced Science and Technology, 2020)
Farming mechanization is primary worry and rising theme for every country. The total populace isexpanding at a quick rate and with increment in populace the requirement for nourishmentincrements energetically. Conventional techniques utilized by ranchers aren't sufficiently adequateto serve the expanding request thus they need to hamper the dirt by utilizing unsafe pesticides in anescalated way. This influence the rural practices a ton and at the last of land stays fruitlesswithenrichens. This review discusses diverse robotization rehearses likeInternet of Things, WirelessCommunications, ML and AI, Deep learning. There were few regions that are making the issuesfarming areas like yield maladies, absence of capacity the executives, weed the board, absence ofwater system and the executives and these issues could be understood by previously said varioussystems. Now, there is a pressing require to disentangle the problems that is utilization ofdestructive pesticides, managed water system, manage on contamination and impacts on conditionin horticultural exercise. Computerization of cultivating rehearses have demonstrated for buildaddition from dirt and its furthermore have fortified dirt ripeness. This reviews shows the efforts ofmultiple scientists to take a short outline related to present execution of computerizationagribusiness. This review likewise examines a planned framework that could be actualized inorganic ranch to blossom and leaf distinguishing proof utilizing IOT